New plastome structural rearrangements discovered in core Tillandsioideae (Bromeliaceae) support recently adopted taxonomy - Vera-Paz, Sandra I.; Díaz Contreras Díaz, Daniel D.; Jost, Matthias; Wanke, Stefan; Rossado, Andrés J.; Hernández-Gutiérrez, Rebeca; Salazar, Gerardo A.; Magallón, Susana; Gouda, Eric J.; Ramírez-Morillo, Ivón M.; Donadío, Sabina; Granados Mendoza, Carolina (Frontiers in Plant Science, 2022)
Full plastome sequences for land plants have become readily accessible thanks to the development of Next Generation Sequencing (NGS) techniques and powerful bioinformatic tools. Despite this vast amount of genomic data, some lineages remain understudied. Full plastome sequences from the highly diverse (>1500 spp.) subfamily Tillandsioideae (Bromeliaceae, Poales) have been published for only three (i.e. Guzmania, Tillandsia, and Vriesea) out of 22 currently recognized genera. Here, we focus on core Tillandsioideae, a clade within subfamily Tillandsioideae, and explore the contribution of individual plastid markers and data categories to inform deep divergences of a plastome phylogeny. We generated 37 high quality plastome assemblies and performed a comparative analysis in terms of plastome structure, size, gene content and order, GC content, as well as number and type of repeat motifs. Using the obtained phylogenetic context, we reconstructed the evolution of these plastome attributes and assessed if significant shifts on the evolutionary trait’s rates have occurred in the evolution of the core Tillandsioideae. Our results agree with previously published phylogenetic hypotheses based on plastid data, providing stronger statistical support for some recalcitrant nodes. However, phylogenetic discordance with previously published nuclear marker-based hypotheses was found. Several plastid markers that have been consistently used to address phylogenetic relationships within Tillandsioideae were highly informative for the retrieved plastome phylogeny and further loci are here identified as promising additional markers for future studies. New lineage-specific plastome rearrangements were found to support recently adopted taxonomic groups, including large inversions, as well as expansions and contractions of the inverted repeats. Evolutionary trait rate shifts associated with changes in size and GC content of the plastome regions were found across the phylogeny of core Tillandsioideae.